2019
DOI: 10.33146/2307-9878-2019-4(86)-155-161
|View full text |Cite
|
Sign up to set email alerts
|

Accounting and Analytical Support of Management of Structural Components of the Enterprise's Potential: Theoretical Aspect

Abstract: Обліково-аналітичне забезпечення управління структурними компонентами потенціалу підприємства: теоретичний аспектРозвиток підприємства значною мірою залежить від спроможності його керівництва приймати оптимальні рішення у напрямку нарощення наявного потенціалу та зміцнення його структурних компонентів. У цьому контексті важливим є організація обліково-аналітичного забезпечення системи управління потенціалом господарюючого суб'єкта. Метою статті є обґрунтування теоретичних засад обліковоаналітичного забезпеченн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Scientist Shkromida N. carried out a complex combined assessment of the components of economic potential, which forms reliable information about the state of production enterprises, and indicated that it is necessary to determine the factors that caused the changes and eliminate them for the future [7].…”
Section: Introductionmentioning
confidence: 99%
“…Scientist Shkromida N. carried out a complex combined assessment of the components of economic potential, which forms reliable information about the state of production enterprises, and indicated that it is necessary to determine the factors that caused the changes and eliminate them for the future [7].…”
Section: Introductionmentioning
confidence: 99%